The impact of the 2008 crisis on the banking sectors of the CEE-11 countries: Multi Level Performance (MLP) score as a synthetic measure of bank risk adjusted performance - Miklaszewska, Ewa; Kil, Krzysztof (Wpływ kryzysu finansowego z roku 2008 na sektory bankowe krajów EŚW – MLP Score jako syntetyczna miara efektywności skorygowanej o ryzyko, 2015)
The aim of this paper was to analyze the long term impact of the 2007-2009 global financial crisis on the banking sectors of CEE countries, in particular in analyzing the consequences of the crisis on bank stability, efficiency and lending policies. Analyzing bank performance and stability, the paper suggests adding a new analytical tool in analyzing risk-adjusted performance: the Multi Level Performance (MLP) Score. The 2008 crisis has illustrated how devastating for the economy the credit crunch could be and how important anti-cyclical lending is for both consumers and businesses. Consequently, in the empirical section the paper analyzes whether the overall performance of the CEE banking sectors, measured, among others, by the MLP Score, was important for loan growth. For the empirical analysis, the paper uses an adjusted dataset on eleven Central and East European Countries (CEE), members of the EU, based on the Bankscope database, employing panel data models for unconsolidated banking data for the 2004-2014 period.
Ekonometria = Econometrics, 2015, Nr 4 (50), s. 126-141
Keywords: CEE banking; bank performance; MLP Score; banki w krajach EŚW; efektywność